The Influence Of Perceptions Of Price And Brand Image On Purchasing Interest (Survey Of MHN Collection Tasikmalaya Koko Shirt Consumers): - Murtadho, Naufal; Barlian, Barin; Arif (Universitas Dehasen Bengkulu, 2024)
This research aims to determine the influence of price perception and brand image on interest in buying Koko MHN Collection Tasikmalaya clothes. The research method used in this research is a quantitative research method with a causality survey method. The types of data used are primary data and secondary data, with a research sample of 100 samples or respondents from MHN Collection Tasikmalaya koko shirt consumers and sampling was carried out using probability sampling with the simple random sampling method. The data analysis tool used is multiple linear regression analysis with the SPSS 26 analysis tool. The results of the research show that price perceptions do not have a positive and insignificant effect on interest in buying MHN Collection Tasikmalaya koko clothes. And the brand image variable has a positive and significant effect on interest in buying MHN Collection Tasikmalaya koko clothes.